The human functioning revolution: implications for health systems and sciences - Bickenbach, Jerome; Rubinelli, Sara; Baffone, Cristiana; Stucki, Gerold (Frontiers in Science, 2023)
The World Health Organization (WHO) concept of functioning represents a new way of thinking about health with wide-ranging consequences. We explicate this paradigm shift, illustrate its potential impact, and argue that societies can profit by implementing functioning as the third indicator of health, complementing morbidity and mortality. Functioning integrates biological health (the bodily functions and structures constituting a person’s intrinsic health capacity) and lived health (a person’s actual performance of activities in interaction with their environment). It is key to valuing health both in relation to individual well-being and societal welfare – operationalizing the Sustainable Development Goal (SDG) 3 principle that health is a public good. Implementing functioning (according to the International Classification of Functioning, Disability and Health; ICF) could profoundly benefit practices, research and policy across health systems and health strategies, and help integrate health and social systems. It also offers a foundation for reconceptualizing multidisciplinary health sciences and for augmenting epidemiology with information derived from peoples’ lived experience of health. A new interdisciplinary science field – human functioning sciences – holds the promise to integrate research inputs and methods from diverse biomedical and social disciplines toward a better understanding of human health. To realize these opportunities we must address formidable methodological, implementation and communication challenges across health systems and broader society. This endeavor is vital to orientate health systems toward what matters most to people about health, to unlock essential societal economic investment in health, and to drive progress toward achieving the SDGs.